2011
DOI: 10.5142/jgr.2011.35.1.092
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glycolipoproteins from Ginseng

Abstract: Ginseng has been used as a general tonic agent to invigorate human body. In the present study, we isolated novel glycolipoproteins from ginseng that activate Ca 2+ -activated Cl -channel (CaCC) in Xenopus oocytes and transiently increase intracellular free Ca 2+ concentration ([Ca 2+ ] i ) in mouse Ehrlich ascites tumor cells. We named the active ingredients as gintonin. Gintonin exists in at least six different forms. The native molecular weight of gintonin is about 67 kDa but its apparent molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(119 citation statements)
references
References 20 publications
3
116
0
Order By: Relevance
“…Gintonin was applied between the third and fourth ATP applications. Gintonin elicited an endogenous Ca 2+ -activated Cl -channel (CaCC) current (Pyo et al, 2011). Gintonin also significantly potentiated the amplitude of subsequent I ATP responses by 2-3-fold, as compared with the third I ATP (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Gintonin was applied between the third and fourth ATP applications. Gintonin elicited an endogenous Ca 2+ -activated Cl -channel (CaCC) current (Pyo et al, 2011). Gintonin also significantly potentiated the amplitude of subsequent I ATP responses by 2-3-fold, as compared with the third I ATP (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…We previously demonstrated that gintonin evoked a [Ca 2+ ] i transient and activated endogenous CaCC in Xenopus oocytes via LPA receptor activation (Hwang et al, 2012;Pyo et al, 2011). Thus, the main action of gintonin is to induce a transient elevation of Ca 2+ from the endoplasmic reticulum, and the re- leased Ca 2+ can subsequently influence diverse Ca 2+ -dependent ion channel and receptor activities (Hwang et al, 2012;Pyo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations